Anatomy of a premise line : how to master premise and story development for writing success - Lyons, Jeff (Focal Press, 2016)
If a story is going to fail, it will do so first at the premise level. Anatomy of a Premise Line: How to Master Premise and Story Development for Writing Success is the only book of its kind to identify a seven-step development process that can be repeated and applied to any story idea. This porcess will save you time, money, and potentially months of wasted writing, so whether you are trying to write a feature screenplay, develop a television pilot, or just trying to figure out your next story move as a writer, this book gives you the tools you need to know which ideas are worth pursuing. In addition to the 7-step premise development tool, Anatomy of a Premise Line also presents a premise and idea testing methodology that can be used to test any developed premise line. Customized exercises and worksheets are included to facilitate knowledge transfer, so that by the end of the book, you will have a fully developed premise line, log line, tagline, and a completed premise-testing checklist.